Bukovyna in the structure of goods export of interwar Romania - Oleksandr Rusnak (Науковий вісник Чернівецького національного університету імені Юрія Федьковича. Історія, 2023)
With each year of the reign of the Romanian authorities, the trade relations of the region expanded. Despite the loss of Bukovyna’s niche in the trade of Austria-Hungary, after World War I it was possible to establish quickly trade circulation both in the middle of Romania and abroad. The geography of business contacts became extremely wide and was not limited to the domestic market, but also included connections with the countries of Europe, Asia and America. Customs in Chernivtsi and Grigore Ghica Vodă (Nepolokivtsi) became the «northern gates of Romania». Growth of trade through them caused the strengthening of the role of the commodity exchange and shops, which allowed Chernivtsi to establish itself as a commercial centre of the region. Grains, poultry, livestock, meat, eggs, skins, fruits, forest and minerals became the export items. The development of the region’s export trade in the specified period was characterized by cyclicality.